SINERGI DIGITAL DALAM MENINGKATKAN MINAT BELI MAHASISWA TERHADAP UMKM MELALUI MEDIA SOSIAL, INFLUENCER, DAN MARKETPLACE - Rina Sundari (Eko dan Bisnis: Riau Economic and Business Review, 2026)
Abstract: This study aims to analyze the influence of digital synergy through social media, influencers, and marketplaces on increasing student purchasing interest in MSME products. The development of digital technology has encouraged MSMEs to utilize various digital platforms as a marketing strategy to reach a wider audience, particularly among students. The research method used was a qualitative method with a purposive sampling approach. The online Google Form questionnaire was distributed to 48 active students at the Riau College of Economics (STIE Riau). Data were analyzed descriptively based on the percentage of respondents' responses to each research indicator. The results indicate that social media plays a significant role in helping students find and understand MSME product information. Furthermore, customer testimonials and review features on marketplaces can increase consumer trust in MSME products. Influencers have also been shown to influence student purchasing decisions, particularly through their credibility in promoting products. Marketplaces provide a positive contribution through promotions and discounts that can increase consumer purchasing interest. Overall, the digital synergy between social media, influencers, and marketplaces has proven effective in increasing student purchasing interest in MSME products.